Antidepressant and neurocognitive effects of serial ketamine administration versus ECT in depressed patients. (April 2020) - Basso, Laura; Bönke, Luisa; Aust, Sabine; Gärtner, Matti; Heuser-Collier, Isabella; Otte, Christian; Wingenfeld, Katja; Bajbouj, Malek; Grimm, Simone
Abstract: Background: While electroconvulsive therapy (ECT) is considered the gold standard for acute treatment of patients with otherwise treatment-resistant depression, ketamine has recently emerged as a fast-acting treatment alternative for these patients. Efficacy and onset of action are currently among the main factors that influence clinical decision making, however, the effect of these treatments on cognitive functions should also be a crucial point, given that cognitive impairment in depression is strongly related to disease burden and functional recovery. ECT is known to induce transient cognitive impairment, while little is known about ketamine's impact on cognition. This study therefore aims to compare ECT and serial ketamine administration not only with regard to their antidepressant efficacy but also to acute neurocognitive effects. Methods: Fifty patients suffering from depression were treated with either serial ketamine infusions or ECT. Depression severity and cognitive functions were assessed before, during, and after treatment. Results: ECT and ketamine administration were equally effective, however, the antidepressant effects of ketamine occurred faster. Ketamine improved neurocognitive functioning, especially attention and executive functions, whereas ECT was related to a small overall decrease in cognitive performance. Conclusions: Due to its pro-cognitive effects and faster antidepressant effect, serial ketamine administration might be a more favorable short-term treatment option than ECT. Limitations: As this research employed a naturalistic study design, patients were not systematically randomized, there was no control group and patients received concurrent and partially changing medications during treatment. Clinical trials registration: Functional and Metabolic Changes in the Course of Antidepressive Treatment, https://clinicaltrials.gov/ct2/show/NCT02099630, NCT02099630.